Modeling Zakāh Contribution to Sustainable Economic Development: Evidence from an Analytic Network Process Framewor - KMT Lasmiatun (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2019)
The purpose of this study is to describe theoretically and empirically zakah as an Islamic financial instrument that has one function to alleviate poverty. The function of zakah is in line with the goal of sustainable economic development which is a form of global commitment in spurring for better economic growth. Research strategy which used in this research is mixed methods with the Analytical Process Networking approach.  Sampling technique used in this research is purposive sampling. Objects in the study include zakah management organizations, academics, government, and practitioners. The findings of this study are that the priority of implementing zakah distribution in supporting sustainable community economic development is the social aspect with a rater agreement W=0.36444. Four strategies can achieve sustainable community economic development, namely Improving the quality and quantity of concern for community social institutions and stakeholders; Improve disaster risk reduction comprehensively and efficiently; Improving the quality of fair law enforcement Increasing job opportunities and concern for community MSMEs.